Regional Economic Integration: Implications on Economic Growth in Nigeria - Chineye, Omolehinwa Linda Udo; Nteegah, Alwell; Kalu, Sylva Ezema (Global Journal of Social Sciences Studies, 2020)
This study investigated the implications of regional economic integration on economic growth in Nigeria over the period 2001 - 2019 using the ARDL methodology. Exports by Nigeria to WAMZ’s member countries as a percentage of total exports, imports to Nigeria from WAMZ’s member countries as a percentage of total import and degree of openness of Nigeria’s economy to WAMZ’s economy are the independent variables while growth rate of GDP was the dependent variable. The findings from the study show that regional economic integration has less implication on economic growth in Nigeria. This is evidenced in the negative relationship between exports to WAMZ member countries by Nigeria and economic growth and the negative relationship between imports from WAMZ member countries to Nigeria and economic growth. Though the degree of openness of Nigeria’s economy to WAMZ’s regional economy was positively related to economic growth in Nigeria both in the short and long runs, the negative link of exports and imports with economic growth and their insignificance show that trade a crucial variable in regional integration has retarding implications on growth in Nigeria over the period. The study attributed similarities in exports and imports among the integrating countries as one major factor that had contributed to the low gain from regional integration by Nigeria and other countries in the region. Based on these findings, the study recommends: openness of the Nigerian economy to WAMZ member countries and the industrialisation of the Nigerian economy as possible measures of increasing gains from regional economic integration.